First Detection and Molecular Characterization of Peach Latent Mosaic Viroid (PLMVd) in Kazakhstan - Gulshan E. Stanbekova; Leila T. Nadirova; Ruslan V. Kryldakov; Bulat K. Iskakov; Andrey V. Zhigailov (Pathogens)
Viroids represent obligate plant pathogens composed exclusively of non-protein coding small single-stranded RNAs that cause high economic losses worldwide. A field survey was carried out to assess the incidence of the peach latent mosaic viroid (PLMVd) in southeastern Kazakhstan, the region of the country where fruit trees are mainly grown. Of 246 stone fruit trees, 20 (8.13%) were infected with the PLMVd. The incidence of the PLMVd in the peach (19.23%; 15/78) was significantly higher than that in the apricot (6.76%; 5/74; p = 0.0234). Eight of the detected viroids were cloned and used for full-genome sequencing. The nucleotide sequence similarity of the selected isolates found in Kazakhstan was 83.9–100%. A phylogenetic analysis indicated three clusters for the Kazakhstani isolates of the PLMVd. Three groups of Kazakhstani viroids differed in their predicted secondary structure. During the survey, the PLMVd was detected and genetically characterized for the first time in Kazakhstan. The obtained results indicate the need to develop state control measures for the PLMVd, including regular monitoring surveys. We identified several SNPs of the PLMVd that had not been previously described. The results may be useful in optimizing diagnostic approaches for detecting stone fruit viroids and preventing their spread through propagation material.